RESEARCH OF PRECAST CONCRETE FRAGMENTS OF PROTECTIVE SHELTERS - Karkhut І. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
This study addresses the construction of modular, quickly assembled reinforced concrete shelters of various classes. The analysis is based on a range of literary, scientific, and technical sources, as well as completed field studies and verification calculations. The author evaluates the advantages and disadvantages of a specific shelter design. The paper includes results from a visual inspection and full-scale testing of a fragment of the protective structure. It provides general information about the design solutions and the outcomes of static tests. The primary goal of the study was to assess the actual technical condition of the shelter and its reliability for its intended purpose. Static calculations established relevant parameters regarding the depth and potential collapse of the shelter to ensure protective properties that align with classes A-I to A-IV. Specific characteristics regarding reinforcement, concrete composition, and wall thickness accompany each respective class. Both visual and instrumental inspections confirmed that the structure met the required geometric dimensions and material specifications outlined in the project and regulatory documents. The test load was calculated at 0.81 of the vertical design load, with no critical damage observed to the shelter ceiling. The study also identified the maximum loads and the primary reasons necessitating design enhancements. Based on the findings from the calculations and full-scale tests, recommendations were developed to improve the reinforcement of prefabricated elements in the protective shelters. Additionally, working drawings were created for the "Varta-3" product, which features enhanced strength against radiation penetration and reduced secondary chipping resulting from blast wave impacts. These improvements were achieved by decreasing the spacing and diameter of the multi-row reinforcement in the shelter's ceiling, thus enhancing the overall concrete structure's performance.